Is distal femoral locking plate the implant of choice to fix all types of Distal femoral fractures? (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine the radiological and functional outcome of different types of distal femoral fractures fixed with locking plates.Methods: This descriptive case series study was conducted at Department of Orthopaedic & Traumatology, Lady Reading Hospital Peshawar from February 2015 to June 2018. Patients of either gender or age with different types of distal femoral fractures fulfilling the inclusion criteria and fixed with distal femoral locking plates were enrolled into the study. Post-operative follow up visits were carried out at 4th week, 6th week and then monthly for 06 months and then every 3rd month till 02 years. Radiological and functional evaluation was done with modified Mize outcome criteria and graded as excellent, good, fair and failure.Results: A total of 107 patients with mean age 44.57 ±SD12.03 years were operated with distal femoral locking plate. Only 6(5.6%) patients were lost to follow up and thus excluded from the study. Male patients were 68(67.3%) while female was 33(32.6%). Intra articular multifragmentary (33-C3) was the predominant fracture present in 29(28.7%) patients. Majority (n=85,8.1%) of the patients had excellent outcome as assessed with modified Mize outcome criteria while good outcome was achieved in 16(15.8%) patients. No non-union or implant failure was reported.Conclusion: Distal femoral locking plates produced an excellent radiological and functional results in majority of the patients with different types of the distal femoral fractures. We recommend locking plate as an implant of first choice to fix all types of the distal femoral fractures.